Policy Objectives Of The Seabed Mining Programme In India - J. V. R. Prasada Rao (International Marine Minerals Society, 1994)
India is dependent for 60% of its annual requirement of copper and the entire quantity of nickel and cobalt on imports from outside the country. Land-based resources are either too meager or of too low a concentration for economic exploitation. This has prompted the country to look to deep seabed re- sources for meeting its rising demand for these metals. The Ocean Policy of the Government of India announced in 1982 talks about the need to map and assess the availability of minerals in the deep sea and to develop necessary technologies for exploration and exploitation of seabed minerals. To be self-reliant such technologies would have to be largely developed, tested and operated indigenously. The adoption of the Law of the Sea Convention in 1982 gave a fillip to India's desire to get into the field of deep seabed mining. India applied for recognition as a Pioneer Investor in Ocean Mining in 1983 and received allotment of a mine site of 150,000 km2 in the Central Indian Ocean in August 1987. Simultaneously, the Government has taken up a programme of development of technologies for exploration of the mine site for resource assessment, environmental monitoring also to meet the commitments like relinquishment of 50% of the area to the Preparatory Commission. Technologies for exploitation of these seabed resource like the mining system, transportation and extractive metallurgy have also been taken up for development in various research institutes largely in the government sector. While India's objective in the long term is to meet the shortage of copper, nickel, cobalt and manganese by the turn of the century, in the short term, the programme aims at application of the seabed mining technologies to meet the immediate needs of the country such as: a. Exploration for oil and natural gas. b. Exploration and exploitation of placer minerals and other deposits at shallow depth in India's EEZ.